Health Professionals and the Dynamics of COVID-19 in Manaus during the First Wave - Bassanezi, R. C.; Takahashi, L. T.; Soares, A. L. O.; Luiz, M. H. R.; De Souza, S. D.; Gomes, D. F. (Trends in Computational and Applied Mathematics, 2022)
A model is made for the dynamics of the transmission of the new SARS-CoV-2 coronavirus, which caused the COVID-19 pandemic. This model is based on the Susceptible--Infectious--Recovered model with heterogeneity in the susceptible population and in the infectious population. The susceptible population is divided into two subpopulations: individuals who are health professionals and individuals who are not. The infectious population is also divided into two subpopulations: individuals who are hospitalized and individuals who are not. A qualitative analysis of the theoretical model is performed, as well as simulations with official data regarding COVID-19 in the city of Manaus, Amazonas, Brazil, which corroborate the profile of the solution curves defined by the model.